Soft Modeling in Predicting Customer Purchase Decision on Plant-Based Product of Start Up Business - Albert, Marcellino (STIE Pelita Nusantara Semarang, 2026)
Many consumers prioritize health, fitness, and social issues, which turns them into wiser purchasing decisions. However, even though vegetarian consumers have appropriate dietary preferences, this does not necessarily guarantee high purchasing decisions for all available plant-based products. This study has developed an empirical model using Pull Push Mooring Theory to be able to explain the purchase decision of plant-based products from start-up companies. This study has developed an empirical model using Pull Push Mooring Theory to be able to explain the purchase decision of plant-based products from start-up companies. This model was tested using empirical data obtained through questionnaires from consumers who have purchased plant-based products from start-up companies. The data obtained were analyzed using Structural Equation Modeling as a data analysis approach. The results of the study show that brand awareness, brand association, perceived quality, and brand loyalty are dimensions of brand equity that have a significant positive effect on purchase intention and customer preference. The results of the study also provide empirical evidence that brand equity, purchase intention and customer preference have a significant positive effect on the purchase decision of plant-based products from start-up companies.